Fremdsprachliches und musikalisches Lernen – Überlegungen zu einem Strukturmodell am Beispiel Islands - Jörg Kessler; Robert Lang (Association Babylonia Switzerland, 2021)
In our paper we introduce our model “Structures of Language and Music” and report about a case study in Iceland. We show how language und music education partly draw from similar concepts in either discipline and how these concepts may be combined for a deeper understanding of language and music learning both in natural as well as in instructed settings. Looking at data collected in a focus group discussion at the University of Iceland and by observations in Icelandic music and foreign language classrooms in an inclusive school in Reykjavík we show in this paper how music and language learning can inspire each other. By understanding the relationship between music and language learning from a more theoretical approach suggested by our model and its reception by specialists from the music and modern languages departments of the University of Iceland as well as its application to classroom practice, we suggest that our model can make a contribution to language and music education as well as teacher education